Effect of molybdenum additions on the microstructures and corrosion behaviours of 316L stainless steel-based alloys. (3rd April 2018) - Rahman, T.; Ebert, W. L.; Indacochea, J. E.
ABSTRACT: Alloys were made by alloying 5, 10, 15, 17.5 and 20 wt-% Mo with Type 316L stainless steel. Sigma phases containing 21–29 wt-% Mo formed along the austenite grain boundaries with the addition of 5 wt-% Mo and increased with additions up to 15 wt-% Mo, but they decreased with further additions. Laves phases containing 33–40 wt-% Mo co-precipitated at additions of 10 wt-% Mo which increased with further Mo increases. The corrosion resistance, assessed by potentiodynamic polarisation in a 10 mM NaCl solution adjusted to pH 4, increased relative to Type 316L for alloys made with 5 and 10 wt-% added Mo, but decreased with further additions due to preferential corrosion of the Laves phase. The alloy made with 10 wt-% added Mo had the highest corrosion resistance due primarily to the high Mo content of the austenite.